2018
DOI: 10.23939/chcht12.01.086
|View full text |Cite
|
Sign up to set email alerts
|

Rheological Behavior of Drilling Fluids Containing Hydrophobically Modified Starch for Filtrate Reduction

Abstract: Abstract.1 In this work, stress-strain graphs of inverse emulsion fluids containing hydrophobically modified starch were plotted from measurements obtained with a coaxial rotating cylinder viscometer, and rheological models were applied. The Bingham model best fitted the experimental results. The correlations obtained by this model allowed calculating plastic viscosity values outside the shear rate sensitivity range of the viscometer and enabled better determination of the conditions for the fluid use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
(33 reference statements)
0
2
0
Order By: Relevance
“…[61] The results showed that the obtained hydrophobic carboxymethyl starch possessed good solubility, salt resistance, and temperature resistance, which can be used as an effective multifunctional additive for water-based drilling fluids. Dias et al [64,70] incorporated lauryl and estearyl units onto the chain of cornstarch by transesterification reaction with vinyl laurate (C-12) or vinyl stearate (C-18) in the presence of a basic catalyst. And then they evaluated the potential of applying those fatty acids-modified starch derivatives as additives to control the filtrate loss in drilling fluids.…”
Section: Starch-based Filtrate Reducersmentioning
confidence: 99%
See 1 more Smart Citation
“…[61] The results showed that the obtained hydrophobic carboxymethyl starch possessed good solubility, salt resistance, and temperature resistance, which can be used as an effective multifunctional additive for water-based drilling fluids. Dias et al [64,70] incorporated lauryl and estearyl units onto the chain of cornstarch by transesterification reaction with vinyl laurate (C-12) or vinyl stearate (C-18) in the presence of a basic catalyst. And then they evaluated the potential of applying those fatty acids-modified starch derivatives as additives to control the filtrate loss in drilling fluids.…”
Section: Starch-based Filtrate Reducersmentioning
confidence: 99%
“…Dias et al. [ 64,70 ] incorporated lauryl and estearyl units onto the chain of cornstarch by transesterification reaction with vinyl laurate (C‐12) or vinyl stearate (C‐18) in the presence of a basic catalyst. And then they evaluated the potential of applying those fatty acids‐modified starch derivatives as additives to control the filtrate loss in drilling fluids.…”
Section: Natural Polymers and Their Derivatives As Filtrate Reducersmentioning
confidence: 99%